2020
DOI: 10.1002/biof.1619
|View full text |Cite
|
Sign up to set email alerts
|

Beyond cholesterol metabolism: The pleiotropic effects of proprotein convertase subtilisin/kexin type 9 (PCSK9). Genetics, mutations, expression, and perspective for long‐term inhibition

Abstract: Proprotein convertase subtilisin/kexin type 9 (PCSK9) has a crucial role in lipid metabolism, particularly due to its function in low‐density lipoprotein receptor degradation. Gain‐of‐function genetic mutations of PCSK9 result in autosomal dominant familial hypercholesterolemia, characterized by high levels of low‐density lipoprotein cholesterol (LDL‐C) and clinical signs of early atherosclerosis. In recent years, PCSK9 has become an important therapeutic target for cholesterol‐lowering therapy. Particularly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 146 publications
0
49
1
Order By: Relevance
“…4.3 Depression and PCSK9. Although it is well established that PCSK9 was discovered in the brain as the human equivalent of NARC-1 (Neural Apoptosis Regulated Convertase-1) implicated in the differentiation of cortical neurons [48], its relationship with the depressive mood has not been clari ed as yet [49,50]. Albeit we found a positive association between BDI-II score and PCSK9, a mutual effect cannot be excluded.…”
Section: Depressioncontrasting
confidence: 69%
See 1 more Smart Citation
“…4.3 Depression and PCSK9. Although it is well established that PCSK9 was discovered in the brain as the human equivalent of NARC-1 (Neural Apoptosis Regulated Convertase-1) implicated in the differentiation of cortical neurons [48], its relationship with the depressive mood has not been clari ed as yet [49,50]. Albeit we found a positive association between BDI-II score and PCSK9, a mutual effect cannot be excluded.…”
Section: Depressioncontrasting
confidence: 69%
“…Besides raised PCSK9 levels, an enhanced CV risk, in our cohort, may be consequent to the increased incidence of insulin resistance and diabetes mellitus. Several studies have shown that insulin, HOMA-IR and HbA1c are correlated with PCSK9 (reviewed in [49]). The link between PCSK9 and insulin resistance has been con rmed in obese individuals undergoing gastric bypass.…”
Section: Depressionmentioning
confidence: 99%
“…Although it is well established that PCSK9 was discovered in the brain as the human equivalent of NARC-1 (Neural Apoptosis Regulated Convertase-1) implicated in the differentiation of cortical neurons [ 48 ], its relationship with the depressive mood has not been clarified as yet [ 49 , 50 ]. Albeit we found a positive association between BDI-II score and PCSK9, a mutual effect cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Besides raised PCSK9 levels, an enhanced CV risk, in our cohort, may be consequent to the increased incidence of insulin resistance and diabetes mellitus. Several studies have shown that insulin, HOMA-IR and HbA1c are correlated with PCSK9 (reviewed in [ 49 ]). The link between PCSK9 and insulin resistance has been confirmed in obese individuals undergoing gastric bypass.…”
Section: Discussionmentioning
confidence: 99%
“…Local steroidogenic activities in the skin have been implicated in the regulation of immune responses at local or systemic levels, and impaired of this cutaneous steroidogenesis has been linked to in ammatory skin disorders [26]. Finally, recent studies have shown that proprotein convertase subtilisin/kexin type 9 (PCSK9), a key regulator of lipid metabolism, may have pro-in ammatory activity on macrophages and has been linked to some markers of systemic in ammation, such as hs-CRP [27]. Nevertheless, there is no evidence to date, on its involvement in HS pathogenesis.…”
Section: Discussionmentioning
confidence: 99%